Developing and Validating a Rasch-Based Scale for Measuring School Counselor Leadership Skills in Aceh Province, Indonesia - Fajriani Fajriani; Yulizar Yulizar (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
School counselor leadership plays a crucial role in strengthening guidance and counseling services, yet there is currently no standardized instrument to measure school counselor leadership skills in Indonesia. This study aims to develop and test the validity and reliability of a scale to assess school counselors’ leadership skills. The instrument was developed through item writing and review based on the Three-Skill Approach, then analyzed using the Rasch Model.  Data were collected from 225 school counselors spread across Aceh Province, Indonesia, with diverse demographic backgrounds. The results indicated that the scale met the assumption of unidimensionality, with 25% of the raw variance explained by the measure. The four-point response scale functioned adequately, and 13 misfit items were identified from 126 items. The scale showed high person and item reliability (above 0.80) with adequate separation indices. Differential Item Functioning (DIF) analysis by gender revealed that most items functioned equivalently, and only 14 items were identified as biased. Overall, the scale demonstrates strong psychometric properties and potential use for assessment and professional development. Further studies are recommended to conduct external validation in broader contexts. Keywords: school counselor, leadership skills, instrument development, validation, rasch model